MUTRASHMARI: REVIEW OF LITERATURE - Waghmode, Sachin; Waghmare, Sachin (International Journal of Research -GRANTHAALAYAH, 2017)
Mutrashmari is a very common disease which includes a complex physiochemical process that involves a series of events in formation of ashmari i.e. stone. Incidence of mutrashmari has raised due to changed standard of living and is strongly associated with race, ethnicity and region of residence. Pathya-apathya is an important factor in mutrashmari. Description of mutrashmari is available in almost all samhita. In Ayurveda, both shaman and shodhanchikitsa is described for the treatment of mutrashmari. Acharya sushrut has mentioned shaman chikitsa like use of ghrita (medicated ghee), taila (medicated oil), paneeyakshara etc. which possess properties like chedana, bhedana, lekhana and mutala before opting for surgical intervention.